Cardiopulmonary Failure Requiring ECMO Bypass Resulting from Leukemia Cell Lysis in a Patient with Childhood Acute Myelomonocytic Leukemia - Michael Huang; Erin Owen; Scott Myers; Ashok Raj (Case Reports in Hematology)
Background. Childhood AML patients are at increased risk for early fatal pulmonary complications. Pulmonary leukostasis and systemic inflammatory response syndrome (SIRS) following leukemia cell lysis are the likely etiologies. Observation. Soon after initiation of AML chemotherapy, an 18-month-old female who met SIRS criteria sustained cardiopulmonary failure requiring ECMO support. Upon recovery, the patient went on to complete therapy and remains in remission without permanent neurologic or cardiac sequelae. Conclusion. Cytokine release syndrome from rapid cell lysis was the likely cause as infectious workup failed to reveal a definitive etiology and drug hypersensitivity testing to the chemotherapy agents was negative.